Recovery of membrane permeability after filtration of sago starch suspension by tangential flow filtration - Carvajal-Zarrabal, O.; S. L. C., Siong; Mohammad Omar, Abdullah; Y. H., Tan; S., Esakie; M. A., Morales-Mora; J., Carrillo-Ahumada; C., Nolasco-Hipólito (Instituto de Ciencias Aplicadas y Tecnología, UNAM, 2023)
Sago starch is extracted from the stems of the sago palm, Metroxylon sagu, in Southeast Asia. A typical Sago starch processing mill in Malaysia generates approximately 20 tons of starch daily containing effluents that can be recovered and marketed to sustain a sm all-scale industry. Tangential flow filtration (TFF) using microfiltration membranes (MFM) has been demonstrated as an effective method for separating suspended solids in biological effluents. When TFF was applied to concentrate the starch from the sago starch suspensions (SSS), the membrane permeability and lifecycle were impacted due to frequent fouling. This study evaluated cleaning methods to recover the permeability and extend the life cycle of MFM following TFF application. Polysulfone membrane filter cassettes of pore size 0.45 μm and surface area 0.1 m2 were each used to separate starch in 100 L of SSS. Following separation, six chemical and physical cleaning methods were tested at laboratory-scale and the degree of cleaning was measured by normalized permeate flux (NPF) and normalized water permeability (NWP). The results showed that soaking the membranes in a 0.2 M NaOH solution (up to 91%, (p<0.05) within a minimum of 72 h, (p<0.05) was the best cleaning method. The procedure has been utilized to maintain and extend the life cycle of the MFM for streams containing starch suspensions.